Association between soluble Notch ligand delta-like ligand 1 and bleeding complications in patients with dengue fever infection - Hildebrand, Dagmar; Nurjadi, Dennis; Hoan, Nghiem Xuan; Linh, Mai Thanh Hai; Sang, Vu Viet; Bang, Mai Hong; Pallerla, Srinivas Reddy; Kremsner, Peter; Heeg, Klaus; Song, Le Huu; Velavan, Thirumalaisamy P. (The journal of infectious diseases, 2022)
Bleeding associated with endothelial damage is a key feature of severe dengue fever. In the current study, we investigated whether Notch ligands were associated with bleeding in 115 patients with confirmed dengue infection in Vietnam. Soluble Notch ligands were determined by means of enzyme-linked immunosorbent assay. Seventeen of 115 patients (14.8%) experienced bleeding manifestations. High soluble delta-like ligand 1 (sDLL1) plasma levels was associated with bleeding (median, 15 674 vs 7117 pg/mL; P < .001). Receiver operating characteristic (ROC) curve analysis demonstrated that sDLL1 had the best test performance (area under the ROC curve, 0.852), with 88% sensitivity and 84% specificity. The combination with alanine aminotransferase and aspartate aminotransferase slightly increased sDLL1 performance. sDLL1 may be useful to guide clinical management of patients with patients in endemic settings.